Archimedes Interdisciplinary Research Programme Forges a Broad Spectrum of Academic Innovations - Michalis Loupis; Georgios Fourlas; Petros Lampsas; Teodoros Tsiftsis; Konstantinos Anagnostou; Nikos Strimpako; Yiannis Raftoyiannis; Anastasia Pantera; Anna Deltsidou (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The basic goal of Archimedes III is to support research teams in Greek Technological Educational Institutes (TEI) and enhance their research capabilities by funding interdisciplinary and inter-institutional research. The programme aims also at attracting talented researchers and developing high quality research personnel. The TEIs, prior to their advancement to the tertiary sector in 2000, focused only on educational activities. Since then, development of research became part of their mission. In order for the Ministry of Education to support TEIsto develop their research capabilities, it designed research programmes targeting exclusively these organisations. Archimedes I and II were designed and ran in the previous programming period (2000-2006) while Archimedes III has been designed in the framework of the Operational Programme "Education and lifelong learning” of the current programming period, 2007-2013. The programme supports research projects in all research fields. However, particular emphasis is given to the fields of engineering and ICT where the main strengths of Greek Technological Educational Institutes are concentrated. The specific project of the TEI of Central Greece, described herewith, comprises 8 research subprojects in fields such as health, environment, energy and ICT with one additional subproject dedicated to management and dissemination. This paper is a comprehensive account of the research objectives and accomplishments of the research project as a whole.
Keywords: O31; 330; Academic Research Incentives; Energy; Environment; Health; ICT